Sudden unexpected death in epilepsy: Investigation of autopsy-based studies - Yan, Fengping; Zhang, Fu; Yan, Yanan; Zhang, Le; Chen, Yuanyuan (Frontiers in Neurology, 2023)
Epilepsy is a common neurological disorder that is associated with increased morbidity and mortality. Sudden unexpected death in epilepsy (SUDEP) is one of the most common causes for epilepsy-related deaths and its characteristics remain largely unknown, particularly from a forensic autopsy perspective. The present study aimed to investigate the neurological, cardiac, and pulmonary findings for a total of 388 SUDEP decedents, encompassing three cases from our forensic center during 2011–2020 and 385 literature-reported autopsy cases. In the cases mentioned in this study, two of them presented with only mild cardiac abnormalities, such as focal myocarditis and mild coronary atherosclerosis of the left anterior coronary artery. The third one was negative of any pathological findings. After pooling together these SUDEP cases, we found that neurological changes (n = 218 cases, 56.2%) were the most common postmortem findings associated with SUDEP, with cerebral edema/congestion (n = 60 cases, 15.5%) and old traumatic brain injury (n = 58 cases, 14.9%) being the major findings. Interstitial fibrosis, myocyte disarray/hypertrophy, and mild coronary artery atherosclerosis were the most common findings related to primary cardiac pathology, documented in 49 (12.6%), 18 (4.6%), and 15 (3.9%) cases, respectively. Non-specific pulmonary edema was the major finding in the lungs. This is an autopsy-based study that reports the scenario of postmortem findings for SUDEP cases. Our study paves the way for understanding the pathogenesis of SUDEP and the interpretation of death.